Investigation of antibacterial properties of novel papain immobilized on tannic acid modified Ag/CuFe2O4 magnetic nanoparticles - (:unkn) unknown (ELSEVIER, 2018)
The non-toxic CuFe2O4 magnetic nanoparticles have been solvothermally synthesized, characterized and used as an efficient magnetic precursor for papain immobilization and then investigated antibacterial properties of them. For increasing the antibacterial activity, the silver nanoparticles were doped on CuFe2O4 magnetic nanoparticles. All prepared samples exhibited stronger antibacterial properties against Gram-positive bacteria (Staphyloccocus aureus) than Gram-negative bacteria (Escherichia coli). However, it was determined that the AgiCuFe(2)O(4) had a more vigorous antibacterial property against the Staphyloccocus aureus bacteria by calculating the inhibition diameter of 25 +/- 0.1 mm in the synthesized samples. Also, the antibacterial activity increased by immobilization of papain. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: CuFe2O4; Tannic acid; Papain immobilization; Silver nanoparticles; Antibacterial activity; FERRITE NANOPARTICLES; SILVER NANOPARTICLES; GRAPHENE; TRYPSIN; FACILE; STABILIZATION; IMPROVEMENT; HYDROLYSIS; REDUCTION; COMPOSITE